ANALISIS PROGRAM PENGEMBANGAN USAHA TANI PADA GENERASI PENGGERAK PERTANIAN (GEGERTANI) DALAM MENINGKATKAN PENDAPATAN PETANI MUSLIM DITINJAU DARI AGRIBISNIS SYARIAH (Studi Kasus Desa Sayang Sedayu Kecamatan Teluk Keramat) - Titin Pratiwi; Wahab, Zulkan (ADISAM PUBLISHER, 2024)
This research is motivatedby an indication that the potential of natural resources owned by Sayang Sedayu Village has a pretty good prospect as a producer of vegetable production thatis quite promosing if the village community future. So, by joining the farmers of Sayang Sedayu Village in Gegertani, can they increase the farmers’ income?. The theory usedinthis research are: 1) Programs, 2). Development, 3). Farming, 4). Organization, 5). Improvement, 6). Income, 7). Sharia Agribusiness. This study uses a descriptive qualitative approach, and includes the type of case study research. Data collection techniques used are observation, interviews, and documentation. Primary data sources are the chairpersons and members of the Agricultural Activator Generation and secondary data are sourced from books, internet, journals, previous research, and archives of the Agricultural Activator Generation. Data analysis teachniques in research are data reduction, data display, and conclusions or verification. The data validity technique used is triangulation and member check. Based on the results of the study concluded that the farming development program, especially in Sayang Sedayu Village, was in the form of providing agricultural facilities and at the beginning of joining the members form Sayang Sedayu Village, they were given a chili demonstration plot, whit this program it can increase the income of gegertani members. Gegertani members, namely the lack of availability of capital from members. In practice, the members are honest, professional in their work, always keep their promises, and are expected to give alms so that in practice it is in accordance with what was exemplified by the prophet Muhammad regarding strategies in sharia business.